Export diversification as a counter to export instability: The example of Columbia - Thomas Mayer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
This paper examines the income and allocation effects of an appropriate export diversification policy by means of a computable general equilibrium model for Colombia. This kind of policy is often envisaged as a counter to unstable export earnings which are considered to be detrimental to economic growth. The results show that irrespective of the reduction of the costs of export instability an appropriate diversification of exports raises income in the Colombian economy.
Keywords: 330